Pembuatan Media Pembelajaran Microsoft Excel Pada Sekolah Menengah Pertama Negeri 2 Tawangmangu - Sri Agustinawati .; Gesang Kristianto Nugroho . (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
ABSTRACT: Teaching system using interactive media is one way to deliver learning materials. Veryprecise delivery of material to assist students in understanding the material presented. Studentlearning system in SMP Negeri 2 Tawangmangu particularly on the subjects of information andcommunication technology is still less than the maximum, because the education system is still simpleexample student worksheets and books - other companion books. To overcome this it is necessary tostudy media can facilitate teachers in delivering learning material.By using media pemebelajaran expected students to quickly grasp the information andcommunication technology lessons and facilitate teachers in presenting the material to students. Inthis study the authors used methods of literature, interview, analysis, design, construct, test thesystem. Hopefully with this learning medium of teaching and learning can help students in SMP Negeri2 Tawangmangu. Further expected learning media can be used by teachers of information andcommunication technology to deliver learning material and can facilitate students in receiving thematerial presented by the teacher.Keywords: Multimedia Learning